Giant cell ependymoma: Cytology of a rare entity with unusual presentation - Kavita Sahai,; Madakasira Sridhar,; Vidushi Joshi,; Neerav Porwal,; Amarinder Singh,; Gaurav Pratap Singh Gahlot, (Indian Journal of Case Reports, 2021)
Giant cell ependymoma (GCE) is a slow-growing tumor that accounts for 9–13% of all ependymoma and occurs preferably at conus medullaris, cauda equina, and filum terminate. Squash cytology is a fast, simple, and reliable technique for intraoperative diagnosis. We present a case of GCE arising at the L5-S2 level and suprasellar region in a 17-year-old male who initially presented with low backache followed by headache and double vision. Intraoperative squash smears of the lumbosacral lesion were suggestive of high-grade glioma. Histomorphological and immunohistochemical profile favors the diagnosis of giant cell variant of myxopapillary ependymoma. He received craniospinal irradiation followed by a boost to the sellar-suprasellar and lumbosacral region through IGMT. After sometime, he developed papilledema and decreased vision, the suprasellar lesion was decompressed which on histopathology revealed similar features. GCE remains a diagnostic challenge on intraoperative squash smears due to its rarity. It has a good prognosis with a 5-year survival of 98.4% after total resection; however, our patient succumbed to illness due to post-operative residual lumbosacral mass and effects of the suprasellar lesion.